KUALITAS PELAYANAN MUTASI PEGAWAI - T. Ardi Dwisasti (Universitas Riau, 2017)
Abstract: Mutations Quality Service Employees. The purpose of research is to analyze thequality of service of a mutation in the civil service in the province of Riau. The study populationare civil servants who receive services BKPPD mutations in Riau Province, consists of 836employees. By using the formula Slovin obtained a total sample of 90 civil servants mutationsservice recipient. The technique of collecting data using questionnaires and interviews. The datawere analyzed using descriptive analysis. The study concluded that the average civil servants whoreceive services mutations are less satisfied with the service BKPPD Riau province, in particularon: the procedure, the fulfillment of technical requirements, process time, equality and justicehandling of the mutation process, competence, guarantee certainty of schedule and feeling safe.